Pogled vrhnjega managementa na izbor orodij internega komuniciranja med uvajanjem sprememb - Sedej, Tanja (Akademija MM, 2013)
At organizations, changes are the only constant; implementing them effectively is a key factor for success. To implement internal communications programs, organizations use a wide range of internal communication tools. Especially in times of change, all tools are not equally suitable; selecting the right ones depends on several factors: what method should they employ to create optimal selection of appropriate tools for communication to support organizational changes. This paper starts with a literature review on communication during the time when changes are introduced in organizations with an emphasis on finding key determinants for modeling the optimal selection of appropriate internal communication tools. The second part is based on empirical research - depth interviews carried out with senior managers of successful companies in Slovenia - it examines the adequacy of the proposed model for selecting internal communication tools during the times when changes are introduced. Indeed, it was revealed that senior managers are aware of the importance and potential of internal communications to alleviate or prevent uncertainty among employees in times of introducing change. Consequently, internal communication tools need to be carefully selected. Within this context, four key selection determinants that lead to the successful change implementation were identified.
Keywords: communication; interno komuniciranje; komuniciranje; management; podjetja; spremembe